A simple method for the estimation of global solar radiation from sunshine hours and other meteorological parameters - Jakhrani, A.Q.; Othman, A.K.; Andrew Ragai, Henry Rigit; Samo, S.R. (IEEE, 2010)
Estimation of solar radiation is considered as the most important parameter for the design and development of various solar energy systems. But, the availability of the required data is very scarce and often not readily accessible. The foremost objective of the present study was to evaluate the various models for the estimation of monthly average global solar radiation from bright sunshine hours and other meteorological parameters at four locations namely Sri Aman, Sibu, Bintulu and Limbang in the Sarawak State. For this purpose, six different solar radiation models, such as Angstrom, Glover, Tasdemirglu, Bahel, Hargreaves and Sayigh, have been investigated. The computed values are compared and assessed, but no relationships of results were found among selected models and with measured values of the nearest location. Hence, a simple and more flexible model is introduced based on the input data of bright sunshine hours, relative humidity and maximum temperature, for the prediction of available global solar radiation on a horizontal surface. The required data for the suggested model is usually available in the most meteorological sites. The proposed model demonstrated acceptable results, and statistically displayed lower RMSE and MBE as compared to the examined models. It could be a good estimator for predicting the global solar radiation in coastal and humid areas.